2021
DOI: 10.1111/dpr.12503
|View full text |Cite
|
Sign up to set email alerts
|

The cancer of corruption and World Bank project performance: Is there a connection?

Abstract: Motivation: Corruption is often cited as a central reason why development projects fail. Purpose: The present paper tests this claim by assessing whether World Bank projects perform worse in implementation environments with a higher corruption level. To avoid pitfalls caused by varying effects of different types of corruption, the paper focuses on one specific form of corruption, namely bribery between public officials and firms during the procurement of needed goods and services. Approach and methods: The nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Some studies have found a positive relationship, others have found no relationship or even a negative relationship. Negative relationships have tended to be most pronounced in studies focused on the Asia‐Pacific region (Bulman et al, 2017 ; Denizer et al, 2013 ; Feeny & Vuong, 2017 ; Feil, 2021 ; Honig et al, 2019 ; Isham et al, 1997 ).…”
Section: Literaturementioning
confidence: 99%
“…Some studies have found a positive relationship, others have found no relationship or even a negative relationship. Negative relationships have tended to be most pronounced in studies focused on the Asia‐Pacific region (Bulman et al, 2017 ; Denizer et al, 2013 ; Feeny & Vuong, 2017 ; Feil, 2021 ; Honig et al, 2019 ; Isham et al, 1997 ).…”
Section: Literaturementioning
confidence: 99%
“…The public sector is first devoted to the common good of society, but fraud and corruption, among others, can be conceived as a true "cancer" and a plague (Feil, 2021). Undoubtedly, these latter phenomena prevent society from achieving this remarkable public goal.…”
Section: Introductionmentioning
confidence: 99%